2016
DOI: 10.15376/biores.11.4.8396-8408
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Removal of COD and Color in Paper-making Wastewater by Ozonation Catalyzed by Fe Supported on Activated Carbon

Abstract: After biological treatment, pulp and paper mill effluent still may contain large amounts of recalcitrant organic pollutants that need to be further treated. In this study, Fe supported on activated carbon (Fe@AC) was prepared and used as a catalyst in the catalytic ozonation of pulp and paper mill effluent. The activity of this catalyst was studied in terms of color and chemical oxygen demand (COD) removal efficiencies. Results showed that the COD removal rate was increased by 21% in the presence of the Fe@AC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…It is also important to note that in the literature there are some controversies regarding the application of kinetic models for the removal of micropollutants viathe implementation of heterogeneous catalytic ozonation. Yong et al [20] considered that ozone can possibly oxidize the pollutant and simultaneously be involved in catalytic reactions with the catalyst surface, resulting in the pseudo-second-order kinetic model, which is in agreement with the findings of other researchers [21,22]. Furthermore, Sumegova et al [16] found that the removal of methylene blue presents better agreement with the second-order kinetic model when zeolite is used as catalyst in the ozonation system, as was also observed by Shokrollahzadeh et al [23], who examined the case of nano-ZnO application as a catalyst for the removal of azo dyes.…”
Section: Resultssupporting
confidence: 79%
“…It is also important to note that in the literature there are some controversies regarding the application of kinetic models for the removal of micropollutants viathe implementation of heterogeneous catalytic ozonation. Yong et al [20] considered that ozone can possibly oxidize the pollutant and simultaneously be involved in catalytic reactions with the catalyst surface, resulting in the pseudo-second-order kinetic model, which is in agreement with the findings of other researchers [21,22]. Furthermore, Sumegova et al [16] found that the removal of methylene blue presents better agreement with the second-order kinetic model when zeolite is used as catalyst in the ozonation system, as was also observed by Shokrollahzadeh et al [23], who examined the case of nano-ZnO application as a catalyst for the removal of azo dyes.…”
Section: Resultssupporting
confidence: 79%
“…Ozone has been employed in the degradation of papermaking wastewater due to its strong oxidation performance, but ozone oxidation alone does not mineralize pollutants to a high degree, so a catalyst is added to improve the ozone oxidation performance. He et al 103 synthesized Fe load activated carbon (AC), which was utilized for catalytic ozonation pulping and papermaking wastewater. Through the analysis of experiments and kinetic models, the Fe@AC/O 3 process of COD removal is 1.6 times the efficiency of AC/O 3 and is 2.1 times ozone alone, and the treatment is better.…”
Section: Pharmaceutical Wastewatermentioning
confidence: 99%
“…In addition, it is also very harmful to water plumbing systems and devices during sewage reuse. [6][7][8] Traditionally, techniques and methods such as biodegradation, advanced oxidation, catalytic oxidation, and photocatalysis are employed in COD and NH 4 + -N removal, [9][10][11][12][13] which are usually time-consuming and high-cost. Adsorption is a conventional and widely used method in low-concentration pollution treatment due to its simple operation, low-cost and high adsorption capacity.…”
Section: Introductionmentioning
confidence: 99%